Knowledge and perceptions of hand hygiene among nurses in a teaching hospital in Pahang - Mohd Ali, Noor Azizah (IIUM Press, 2025)
Background: Healthcare-associated infections (HAIs) frequently commonly occur in hospitalised patients, yielding various consequences, including extended inpatient stays, increased microbial resistance to antimicrobial agents, and potentially substantial mortality rates. Emphasising the paramount significance of hand hygiene, it is considered the primary preventive measure against the dissemination of infectious agents. However, hand hygiene compliance among staff nurses and other healthcare workers (HCWs) was still low partly due to the lack of hand hygiene knowledge and it is able to have a significant impact on patients’ health status. The objective of this study is to assess knowledge and perceptions of hand hygiene among staff nurses in a new teaching hospital. Methods: This quantitative study used a convenience sampling method in which nurses were invited from three critical care areas and five non-critical care areas. Data were collected through a self-administered questionnaire, and Statistical Package for Social Science (SPSS) was used for data analysis. Results: The majority of staff nurses (88.9%) had moderate knowledge with a mean score=66.6 (SD±7.4). Although there was no significant difference between the sociodemographic characteristics of nurses (age, gender, department, received formal hand hygiene training, and routinely used alcohol-based hand rub) (p>0.05) and the knowledge level of nurses, this study found that the nurses have good perceptions about hand hygiene 79.8%. Conclusion: This study highlights the knowledge of hand hygiene at a moderate level across critical and non-critical areas. Thus, the study suggests the need for targeted interventions to enhance hand hygiene knowledge among healthcare personnel, thereby contributing to improve patient outcomes.